Investigation On Hybrid Geometric Modelling Construction For Injection Mould Using CAD System - Abdul Malek, Noor Atikah (Universiti Sains Malaysia, 2018)
The use of injection moulding process is becoming more popular recently due to its profitable returns in plastic manufacturing industry. Its flexibility in changing the product type have made injection-moulding process widely used. Time consuming and complexity in designing the injection mould has led to developing a hybrid geometric modelling construction that can be used in designing a mould with CAD system for injection moulding process.A system that consist of a combination of two representation schemes will produce a mould design from the product part model. The algorithm for the two representation schemes are integrated to produce a hybrid scheme that later can generate mould design without a complex way. This research is aiming on simplified the current method in creating the core and cavity for the mould. At the end of this study, the developed algorithm able to detect the topology for the part model. It able to recognise the characteristic of the model and interpret it in form of topology data. Then, it can develop a design for pair of core and cavity for injection mould. The designing work for mould can be simplified.